ANALYSIS OF THYMUS DISEASE INCIDENCE IN KHARKIV REGION WITHIN THE PERIOD OF 1990-2005 - Protsenko, E.S.; Remnyova, N.A.; Ponomaryov, A.O (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
For the first time, the structure of thymus disease incidence in Kharkiv region within the period of 1990-2005 was investigated and analyzed. Two hundred and forty four cases of thymus diseases (173 women and 71 men) were registered during this period. The most frequent disease of the thymus in women is hyperplasia, in men – lymphoepithelial thymoma.